Factors Influencing Business Angel’s Investment Decision - Linh, Nguyen Thi Phuong (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 35 No 4, 2019)
The article provided some factors influencing angel’s investment decisions. Using secondary data from official sources, the author analyzed the impact of factors based on two perspectives: the perspective from startup and the perspective from the government and the business environment. The author provided examples of some countries to illustrate each group of factors. Based on that, the article has made suggestions for startups to fully prepare for calling angel investor successfully, and also suggesting some policy implications for the government improving the business environment in order to promote angel investments.